LAJU PERTUMBUHAN KARANG Acropora formosa YANG DITRANPLANTASI PADA MEDIA TEMPEL DAN MEDIA GANTUNG - Stevania M Runtuwene; Indri S Manembu; Noldy G.F Mamangkey; Antonius P Rumengan; Darus Paransa; Hariyani Sambali (Sam Ratulangi University, 2020)
Corals are associations of millions polyps that live in symbiotic way with zooxanthellae algae. Most of the polyps live in colonies and form a reef. Coral reefs are rich ecosystems that contain diverse organisms living in it. However, the threat of damage increases with the pressure that enters the waters. Coral transplantation is one way of restorations that can be done to restore damaged corals by cutting live corals and then planting them in places where the corals have been damaged. This study aims to determine the growth rate of Acropora formosa corals that were transplanted on fixed and hanging media. Data was collected in Malalayang Coast Waters, Manado City, North Sulawesi. The research took place for seven months. Beginning with the coral transplant activity of Acropora formosa on fixed and hanging media, then continued with monitoring every month for six months. Transplanted corals were measured using a ruler to determine the length of the coral from the beginning to the end of the study and then the data was analyzed using Microsoft Excel. The results obtained for the average growth rate of Acropora formosa corals transplanted on fixed media were 0.8 cm and on hanging media 1.8 cm. Overall growth rate averaged 1.3 cm.Keywords: Coral, Coral Reef, Transplant, Acropora formosa.